2015
DOI: 10.1111/meca.12081
|View full text |Cite
|
Sign up to set email alerts
|

Distribution‐Utilization Interactions: A Race‐to‐the‐Bottom Among Oecd Countries

Abstract: We explore four decades of short‐ and long‐run interactions between income distribution and real economic activity for a panel of OECD countries. Our regressions suggest that the dynamic interaction of these two variables is rather complicated. Estimating the long‐run point, we argue that this equilibrium has been shifting as a matter of public policy. We hypothesize that a race‐to‐the‐bottom arises from a need to be competitive in globalized markets. We report evidence that globalization does have a negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…These findings appear to hold for other countries. Hogrefe and Kappler (2013) and Rada and Kiefer (2016) show similar results on the basis of econometric analysis for OECD countries. Unlike Elsby et al (2013), the latter authors also find that union density remains a fairly robust correlate of the labor share even when including an index of globalization.…”
Section: Discussion: Baumol Lewis and Stagnationsupporting
confidence: 57%
See 1 more Smart Citation
“…These findings appear to hold for other countries. Hogrefe and Kappler (2013) and Rada and Kiefer (2016) show similar results on the basis of econometric analysis for OECD countries. Unlike Elsby et al (2013), the latter authors also find that union density remains a fairly robust correlate of the labor share even when including an index of globalization.…”
Section: Discussion: Baumol Lewis and Stagnationsupporting
confidence: 57%
“…These findings appear to hold for other countries. Hogrefe and Kappler (2013) and Rada and Kiefer (2016) show similar results on the basis of econometric analysis for OECD countries. Unlike Elsby et al .…”
Section: Baumol and Lewis: Structural Change Stagnation And The Labor Share Of Incomementioning
confidence: 58%
“…These findings appear to hold for other countries. Hogrefe and Kappler (2013) and Rada and Kiefer (2016) show similar results on the basis of econometric analysis for OECD countries. Unlike Elsby et al (2013), the latter authors also find that union density remains a fairly robust correlate of the labor share even when including an index of globalization.…”
Section: Discussion: Baumol Lewis and Stagnationsupporting
confidence: 57%
“…On the other hand, Hein and Vogel (2009) and Stockhammer and Onaran (2012) have found wage-led results. Nikiforos and Foley (2012) have shown that non-linearities are of great importance, while Rada and Kiefer (2015) find empirically that, in accordance with numerical results by von Arnim et al (2014), global demand looks wage-led even though individual countries appear to be profit-led. From a theoretical standpoint, whether demand and growth are wage-led or profit-led (or neither) in the short run depends on the shape of the investment function.…”
Section: Related Literaturesupporting
confidence: 61%